Moral competence in nursing practice - Pantip Jormsri (2018)
This article presents the derivation of moral competence in nursing practice by identifying its attributes founded on Thai culture. In this process moral competence is formed and based on the Thai nursing value system, including personal, social and professional values. It is then defined and its three dimensions (moral perception, judgment and behavior) are also identified. Additionally, eight attributes as indicators of moral competence are identified and selected from three basic values. The eight attributes are loving kindness, compassion, sympathetic joy, equanimity, responsibility, discipline, honesty, and respect for human values, dignity and rights. All attributes are discussed by addressing the three moral dimensions in order to present how to deal with ethical issues in nursing practice. As a summary, a model of moral competence is presented to demonstrate moral competence in nursing practice in Thailand. © 2005 Edward Arnold (Publishers) Ltd.